2018
DOI: 10.1001/jamasurg.2018.1050
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Pediatric Trauma Field Triage

Abstract: It is crucial to transport the right patient to the right hospital. Yet the quality of the full diagnostic strategy to determine the optimal receiving hospital is unknown. None of the investigated field triage protocols complied with current sensitivity targets. Improved efforts are needed to develop accurate child-specific tools to prevent undertriage and its potential life-threatening consequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…In a recent review including five studies with a combined number of 1222 pediatric patients requiring specialized trauma care, the sensitivity of the prehospital triage tools ranged from 49.1 to 87.3% to correctly identify pediatric major trauma patients. This corresponded to under triage rates between 12.7 and 50.9% [10]. An under triage higher than 20% was also reported in the Western USA between 2006 and 2008 for children 0 to 10 years of age and 11 to 20 years of age with a major trauma (ISS > 15) [17].…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…In a recent review including five studies with a combined number of 1222 pediatric patients requiring specialized trauma care, the sensitivity of the prehospital triage tools ranged from 49.1 to 87.3% to correctly identify pediatric major trauma patients. This corresponded to under triage rates between 12.7 and 50.9% [10]. An under triage higher than 20% was also reported in the Western USA between 2006 and 2008 for children 0 to 10 years of age and 11 to 20 years of age with a major trauma (ISS > 15) [17].…”
Section: Discussionmentioning
confidence: 65%
“…It seems that high under triage rates are common in the pediatric population in diverse settings [19]. In fact, several studies reported unacceptable under triage rates even when using specific pediatric algorithms [10]. These observations seem to mirror the complexities of the triage process itself between the constraints of the triage tool, prehospital provider experience and judgement, and trauma center proximity and capacity [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations